Association between Perceived Seriousness, Cues to Action, and Voluntary Counseling and Testing Uptake in Men Who Have Sex with Men in Pematangsiantar, North Sumatera - Lambok Nita Situmorang; Lita Sri Andayani; Linda T Maaas (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Utilization of voluntary counseling and testing (VCT) services in male sex with men (MSM) at Tomuan public health center, in Pematangsiantar is still relatively low (34.4%). The low utilization of VCT services in MSM is related to the perception of seriousness and the possibility of taking action. This study aimed to analyze the influences of perceived seriousness and cues to action on the use of VCT in MSM.Subjects and Method: This was a cross sectional study carried out at Tomuan health center in Pematangsiantar, North Sumatera, in 2017. A sample of 61 MSM was selected for this study. The dependent variable was VCT use. The independent variables were perceived seriousness and cues to action. The data were obtained by questionnaire and analyzed by a multiple logistic regression.Results: Utilization of VCT in MSM increased with perceived seriousness (OR= 11.28; 95% CI= 1.24 to 102.89; p=0.032) and cues to action (OR= 11.45; 95% CI= 1.02 to 128.34; p= 0.024).Conclusion: Utilization of VCT in MSM increases with perceived seriousness and cues to action.Keywords: perceived seriousness, VCT utilizationCorrespondence: Lambok Nita Situmorang. Masters Program in Public Health, Faculty of Public Health, Universitas Sumatera Utara, Jl. Prof. T. Maas, Medan, North Sumatera. Email: nithastmoors@gmail.com. Mobile: 085372537900.Journal of Health Promotion and Behavior 4(2): 121-125https://doi.org/10.26911/thejhpb.2019.04.02.04